Ternary diffusion in aqueous sodium salicylate + sodium dodecyl sulfate solutions - Melia Rodrigo, M. (2022)
A Taylor dispersion method has been used to measure ternary mutual diffusion coefficients (D11, D22, D12 and D21) in aqueous sodium salicylate (NaSal) (component 1) + sodium dodecyl sulfate (NaDS) (component 2) solutions at 25.00 °C and concentrations up to 0.050 mol dm−3. In general, the data show that diffusion of NaDS drives co-current flow of NaSal, and that diffusion of NaSal drives also co-current flows of NaDS. The experimental ternary diffusion coefficients are compared with Nernst-Planck coefficients allowing a better interpretation of the electrostatic mechanism for the coupled diffusion of NaSal and SDS. From these equations, at compositions below the critical micelle concentration (cmc) of NaDS, small positive values of D12 and D21 are obtained resulting from fully dissociation of NaDS; however, at compositions above the cmc, the coupled diffusion of NaSal and NaDS becomes significant, as indicated by the experimental and predicted large positive cross-diffusion coefficients, D21. There is a good agreement between our data and those predicted by the Nernst-Planck equations for NaDS concentrations below and above the cmc.